Polypropylene-based compound as well as preparation method and application thereof

By in-situ composite gamma alumina nanosheets in polypropylene and optimizing their preparation process, the problem of insufficient dispersion of nanosheets is solved, and the dielectric constant and breakdown field strength of the composite material are significantly improved. It is suitable for high voltage and high storage Energy field.

CN119391076AActive Publication Date: 2025-02-07XI AN JIAOTONG UNIV +4
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411557951.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The nanosheet dispersion of existing polypropylene/nanocomposites is insufficient, the preparation process needs to be optimized, and the relationship between the composite material performance and nanosheet content and size is unclear, which limits its application in the fields of high-pressure and high energy storage.

Method used

The gamma alumina nanosheets were used to combine gamma alumina nanosheets with polypropylene in situ to prepare gamma alumina nanosheets by optimizing hydrothermal reaction and sintering to improve their dispersion and performance in the polypropylene matrix.

Benefits of technology

显著提高了复合材料的介电常数和击穿场强,实现了更高的绝缘性能,适用于高压、高储能领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391076A_ABST
    Figure CN119391076A_ABST
Patent Text Reader

Abstract

The invention discloses a polypropylene-based compound as well as a preparation method and application thereof. The compound comprises 95-99.5 wt% of polypropylene and 0.5-5 wt% of gamma aluminum oxide nanosheets. Specifically, gamma aluminum oxide nanosheets are compounded into polypropylene to obtain the compound, so that the dielectric constant and the breakdown field strength of the compound are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials and relates to a polypropylene-based composite material, a preparation method and an application thereof. Background Art

[0002] As energy demand continues to grow, power systems have increasingly higher requirements for composites. In power systems, polypropylene (PP), as an important composite, is widely used in cable insulation, capacitor films and other fields. However, the breakdown field strength and energy storage density of pure polypropylene materials are relatively low, which limits its application in high-voltage and high-energy storage fields.

[0003] In recent years, nanocomposites have attracted wide attention due to their excellent physical and chemical properties. Although researchers have achieved certain results in polypropylene / nanocomposites, the following problems still exist: the dispersion of nanosheets in the polypropylene matrix needs to be improved to give full play to the performance advantages of nanosheets; the preparation process of composite materials needs to be optimized to achieve large-scale production; the relationship between the performance of composite materials and factors such as nanosheet content and size is not clear and needs further study.

[0004] In response to existing problems, it is urgent to optimize the preparation process and study the influence of factors such as nanosheet content and size on the performance of composite materials, so as to provide a theoretical basis for the research and application of high-performance polypropylene-based composites. Summary of the invention

[0005] In order to overcome the above problems, the present invention proposes a polypropylene-based composite, a preparation method and an application thereof, wherein the composite comprises 95-99.5wt% of polypropylene and 0.5-5wt% of γ-alumina nanosheets. Specifically, the γ-alumina nanosheets are in-situ compounded into polypropylene to obtain the composite, so that the dielectric constant and breakdown field strength of the composite are improved, thereby completing the present invention.

[0006] Specifically, the purpose of the present invention is to provide the following aspects:

[0007] In a first aspect, a polypropylene-based composite is provided, wherein the composite comprises 95-99.5 wt % of polypropylene and 0.5-5 wt % of γ-alumina nanosheets.

[0008] Wherein, the length of the γ-alumina nanosheets is 119-163 nanometers.

[0009] Wherein, the thickness of the γ-alumina nanosheet is 8-10 nanometers.

[0010] The composite is obtained by in-situ compounding of γ-alumina nanosheets into polypropylene.

[0011] In a second aspect, a method for preparing the composite of the first aspect is provided, the method comprising:

[0012] Step 1, dissolving polypropylene pellets in an organic solvent to obtain a first solution;

[0013] Step 2, adding a suspension containing γ-alumina nanosheets to the first solution to obtain a second solution;

[0014] Step 3, purifying the second solution to obtain the complex.

[0015] In step 1, the organic solvent is selected from one or more of decahydronaphthalene, toluene and xylene.

[0016] In step 1, the dissolution temperature of the polypropylene pellets in the organic solvent is 90-110°C.

[0017] In step 3, the purification includes: filtration, extraction and drying.

[0018] Wherein, acetone is used for filtration.

[0019] In a third aspect, use of the composite material described in the first aspect or the composite material prepared by the method described in the second aspect in polypropylene-based composite films.

[0020] The beneficial effects of the present invention include:

[0021] (1) The polypropylene-based composite proposed in the present invention is in-situ doped with polypropylene and γ-alumina nanosheets, so that the dielectric constant and breakdown field strength of the composite are improved.

[0022] (2) The γ-alumina nanosheets contained in the polypropylene-based composite proposed in the present invention are prepared by staged drying and staged sintering to obtain a complete nanosheet structure, thereby improving the performance of the composite. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.

[0024] In the attached picture:

[0025] FIG1 (a) shows one of the TEM characterizations of the γ-alumina nanosheets prepared in Example 1;

[0026] FIG1( b ) shows the second TEM characterization of the γ-alumina nanosheets prepared in Example 1;

[0027] FIG1( c ) shows the TEM characterization of the γ-alumina nanosheets prepared in Comparative Example 1;

[0028] Figure 2 A comparison chart of dielectric constants and material loss spectra of the polypropylene-based composite films prepared in Examples 1-4 and the polypropylene film prepared in Comparative Example 2 is shown;

[0029] Figure 3 The Weibull distribution diagrams of DC breakdown of the polypropylene-based composite films prepared in Examples 1-4 and the polypropylene film prepared in Comparative Example 2 are shown. DETAILED DESCRIPTION

[0030] The following will refer to the attached Figure 1(a) to Figure 3 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0031] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0032] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0033] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.

[0034] In one aspect, a polypropylene-based composite is provided according to the present invention, comprising 95-99.5 wt % of polypropylene and 0.5-5 wt % of γ-alumina nanosheets.

[0035] Among them, polypropylene is used as the matrix material, and the γ-alumina nanosheets play a role in blocking discharge, inhibiting breakdown development and hindering the growth of electrical dendrites in the composite system. Low mass concentration doping can improve the insulation performance of polypropylene-based composites. Preferably, the composite includes 99-99.5wt% polypropylene and 0.5-1wt% γ-alumina nanosheets; more preferably, the composite includes 99.5wt% polypropylene and 0.5wt% γ-alumina nanosheets.

[0036] In the present invention, the γ-alumina nanosheets have a thickness of 8 to 10 nanometers and a length of 119 to 163 nanometers.

[0037] In a second aspect, a method for preparing a polypropylene-based composite is provided according to the present invention, the method comprising: in-situ compounding γ-alumina nanosheets into polypropylene to obtain the composite.

[0038] According to a preferred embodiment, the method specifically comprises the following steps:

[0039] Step 1, dissolving polypropylene pellets in an organic solvent to obtain a first solution;

[0040] Step 2, adding a suspension containing γ-alumina nanosheets to the first solution to obtain a second solution;

[0041] Step 3, purifying the second solution to obtain the complex.

[0042] Specifically:

[0043] Step 1, dissolving polypropylene in an organic solvent to obtain a first solution.

[0044] In step 1, the organic solvent is preferably selected from one or more of decahydronaphthalene, toluene, and xylene, preferably xylene.

[0045] The organic solvent is used to dissolve polypropylene pellets, and the polypropylene pellets have excellent solubility in xylene.

[0046] Furthermore, the mass ratio of the polypropylene pellets to the volume ratio of the organic solvent (g:mL) is 1:(90-150), preferably 1:(95-110), for example 1:100.

[0047] Among them, the solubility of polypropylene pellets in organic solvents is limited, so more organic solvents are needed to ensure that the polypropylene pellets can be fully dissolved. Too much organic solvent may reduce the reaction rate of the reaction system.

[0048] In step 1, polypropylene pellets are dissolved in an organic solvent and fully dissolved at 90-110°C, such as 100°C.

[0049] The polypropylene in the polypropylene pellets is a non-polar polymer, and its solubility in organic solvents increases with increasing temperature. Within the temperature range of 90-110°C, it is sufficient for polypropylene to be fully dissolved in organic solvents.

[0050] Step 2: adding a suspension containing γ-alumina nanosheets into the first solution to obtain a second solution.

[0051] In step 2, the suspension containing γ-alumina nanosheets uses one or more of decahydronaphthalene, toluene and xylene as solvent, preferably the same as the organic solvent selected in step 1, such as xylene, to avoid the influence of other impurities on the reaction system.

[0052] The γ-alumina nanosheets are dispersed in the solvent in advance to improve the dispersibility of the γ-alumina nanosheets in the first solution. In order to disperse the γ-alumina nanosheets in the solvent as evenly as possible, the ultrasonic treatment is preferably performed for 2 to 3 hours, for example, 2 hours.

[0053] In step 2, the concentration of the γ-alumina nanosheets in the solvent is not strictly limited.

[0054] In step 2, the mass of the γ-alumina nanosheets is 0.5-5wt% of the total mass of the polypropylene and the γ-alumina nanosheets, preferably 0.5-1wt%, and more preferably 0.5wt%.

[0055] In step 2, a suspension containing γ-alumina nanosheets is added to the first solution and stirred for 2 to 4 hours to improve the dispersibility of the γ-alumina nanosheets in the first solution.

[0056] The inventors found that the gamma alumina nanosheets obtained in the prior art have fuzzy edges, pores and irregular shapes. The inventors prepared the gamma alumina nanosheets by optimizing the hydrothermal reaction and the sintering method to improve the quality of the gamma alumina nanosheets.

[0057] In a preferred embodiment, the γ-alumina nanosheets are prepared by the following method:

[0058] Step 2-1, dissolving aluminum salt and adjusting to obtain a liquid with a pH of 4.8 to 5.1;

[0059] Step 2-2, hydrothermally treating the liquid to obtain a first product;

[0060] Step 2-3, sintering the first product to obtain the γ-alumina nanosheets.

[0061] In step 2-1, the aluminum salt is selected from one of aluminum carbonate, aluminum acetate, and aluminum sulfate 18hydrate powder, preferably aluminum sulfate 18hydrate powder.

[0062] Among them, water is preferably used to dissolve the aluminum salt, and the aluminum salt can easily form a solution in water, which is conducive to the subsequent steps. Aluminum sulfate 18hydrate powder is usually of high purity and contains fewer impurities, which is helpful for preparing high-purity aluminum oxide nanosheets; more importantly, the crystal water in the aluminum sulfate 18hydrate powder can be released during the heat treatment process, which is helpful for forming porous aluminum oxide nanosheets.

[0063] In step 2-1, the concentration of the aluminum salt in water is 0.8-0.12 mol / L, for example, 1 mol / L.

[0064] In step 2-1, the aluminum salt is stirred in water at a rate of 1000-2000 r / min for 1-5 h; preferably, at a rate of 1400-1600 r / min for 2-4 h; for example, at a rate of 1500 r / min for 3 h to obtain a uniform solution.

[0065] In step 2-1, since soluble aluminum salts are usually highly acidic, a weak base is usually used to adjust the pH. At this time, the aluminum hydroxide precursor formed by the reaction of the aluminum salt is suspended in water, that is, the liquid obtained at this time appears as a suspension.

[0066] In step 2-1, the pH is 4.8 to 5.1, for example 5.0. If the pH is greater than 7, a rod-shaped material will be obtained.

[0067] In step 2-1, a weak base is helpful for adjusting the pH, and ammonia water is preferred for easy removal.

[0068] In step 2-2, the aluminum hydroxide precursor is converted into aluminum oxide through hydrothermal treatment.

[0069] In step 2-2, the temperature of the hydrothermal treatment is 180-200°C, preferably 185-195°C, for example 190°C.

[0070] In step 2-2, the hydrothermal treatment time is 18 to 36 hours, preferably 24 to 38 hours, for example 24 hours.

[0071] The temperature and time of the hydrothermal treatment can obtain γ-alumina nanosheets with a sheet-like structure.

[0072] In step 2-2, the hydrothermal treatment is preferably carried out in a high-pressure reactor.

[0073] In step 2-2, after hydrothermal treatment, the first product is obtained by washing and drying.

[0074] Among them, it is preferred to use water to wash to neutrality to remove impurities, unreacted weak base such as ammonia water and impurities soluble in water.

[0075] In step 1-2, the drying is staged drying, including:

[0076] The first stage: drying at 25-40℃ for 3-6h;

[0077] The second stage: drying at 50-65℃ for 6-10h;

[0078] The third stage: drying at 70~100℃ for 10~15h.

[0079] Further preferably, the drying comprises:

[0080] Stage 1: Dry at 30-35°C for 4-5 hours;

[0081] The second stage: drying at 55-60℃ for 7-8h;

[0082] The third stage: drying at 80~85℃ for 11~13h.

[0083] Most preferably, the drying comprises:

[0084] Stage 1: drying at 30°C for 4h;

[0085] The second stage: drying at 60°C for 8h;

[0086] The third stage: drying at 80°C for 12h.

[0087] In step 2-3, the sintering is carried out in stages, including:

[0088] Stage I: Heating from room temperature to 110-140 °C at a rate of 6-15 °C / min, and keeping at this temperature for 0.3-1.5 h;

[0089] Stage II: Heating to 260~320℃ at a rate of 8~20℃ / min, and keeping at this temperature for 0.3~1h;

[0090] Stage III: Heating to 430-480°C at a rate of 6-15°C / min, and keeping at this temperature for 0.3-2h;

[0091] Stage IV: Heat to 570~630 ℃ at a rate of 8~20 ℃ / min, and keep at this temperature for 0.5~2h; then cool naturally to room temperature.

[0092] Among them, staged sintering helps to control the reaction rate and the speed of product overflow, thereby obtaining better product morphology.

[0093] Further preferably, the sintering includes:

[0094] Stage I: Heating from room temperature to 115-130 °C at a rate of 8-10 °C / min, and keeping at this temperature for 0.3-1h;

[0095] Stage II: Heating to 280~310℃ at a rate of 9~11℃ / min, and keeping at this temperature for 0.5~1h;

[0096] Stage III: Heating to 440-460°C at a rate of 8-10°C / min, and keeping at this temperature for 0.3-1.5h;

[0097] Stage IV: Heat to 580~620 ℃ at a rate of 9~11 ℃ / min, and keep at this temperature for 0.6~1.2h; then cool naturally to room temperature.

[0098] More preferably, the sintering includes:

[0099] Stage I: Heating from room temperature to 120 °C at a rate of 10 °C / min, and keeping at this temperature for 0.5 h;

[0100] Stage II: Heating to 300 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0101] Stage III: heating to 450 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0102] Stage IV: Heat to 600 °C at a rate of 10 °C / min and keep at this temperature for 0.5 h; then cool naturally to room temperature.

[0103] Step 3, purifying the second solution to obtain the complex.

[0104] In step 3, the purification includes: filtration, extraction and drying.

[0105] In step 3, acetone is preferably used for suction filtration. Acetone has relatively high volatility, which is conducive to rapid removal; and acetone has high solubility, which can effectively remove residual organic solvents and other organic impurities in polypropylene.

[0106] In step 3, preferably, extraction is performed in deionized water using a Soxhlet extractor.

[0107] In step 3, the drying is preferably freeze-drying, and the drying time is not strictly limited, usually 25 to 48 hours.

[0108] In a third aspect, according to the present invention, there is provided a polypropylene-based composite film, wherein the composite film uses a polypropylene-based compound as a filler and a polyimide film as a matrix, and is obtained by heat pressing.

[0109] In the present invention, the polyimide film should have an appropriate thickness and size so as to completely wrap the biaxially oriented composite material in the subsequent hot pressing process, and the thickness is usually selected to be 100-150 μm.

[0110] In the present invention, the temperature of hot pressing is 190-220° C., the time is 8-10 min, and the pressure is 15-20 MPa; for example, the temperature is 210° C., the time is 10 min, and the pressure is 15 MPa.

[0111] In the present invention, the dielectric constant of the composite film ranges from 2.2 to 2.45, with a maximum dielectric constant of 2.45; the breakdown field strength ranges from 481 to 625 kV / mm, with a maximum of 625 kV / mm.

[0112] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.

[0113] Example 1

[0114] (1) Preparation of γ-alumina nanosheets:

[0115] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;

[0116] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral. The product was then dried in a vacuum oven at 30°C for 4 h, 60°C for 8 h, and 80°C for 12 h to obtain the first product.

[0117] The first product is placed in a muffle furnace in an air atmosphere and sintered in the following stages:

[0118] Stage I: Heating from room temperature to 120 °C at a rate of 10 °C / min, and keeping at this temperature for 0.5 h;

[0119] Stage II: Heating to 300 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0120] Stage III: heating to 450 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0121] Stage IV: Heat to 600 °C at a rate of 10 °C / min and keep at this temperature for 0.5 h; then cool naturally to room temperature.

[0122] After the above steps are completed, the γ-alumina nanosheets are prepared for use.

[0123] (2) Dissolve 5 g of polypropylene pellets in 500 mL of xylene at 100°C to obtain a first solution; dissolve 0.025 g of the γ-alumina nanosheets prepared in step (1) in 10 ml of xylene (the mass of the γ-alumina nanosheets is 0.5 wt% of the total mass of the polypropylene and the γ-alumina nanosheets), and disperse them by ultrasonic dispersion for 2 h to obtain a suspension containing γ-alumina nanosheets; use a pipette to drop the above suspension of γ-alumina nanosheets into the first solution one by one, stir for 2 h, and obtain a second solution; after the reaction is completed, pour the obtained product into acetone for suction filtration, and use a Soxhlet extractor to extract in a deionized water environment for 24 h, and then freeze-dry for 48 h to obtain a polypropylene-based composite.

[0124] (3) A circular cutter with a diameter of 50 mm was used to cut a number of circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm. A second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film. 0.2 g of the biaxially oriented composite material was placed in the circular holes of the first polyimide film. A third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it. Then, a flat-plate vulcanizer was used for hot pressing treatment. The temperature was set to 210 °C, the pressure was set to 15 MPa, the processing time was set to 10 min, the number of exhaust times was set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene-based composite film.

[0125] Example 2

[0126] A polypropylene-based composite film was prepared in a similar manner to Example 1, except that the mass of the γ-alumina nanosheets was 1 wt % of the total mass of the polypropylene and the γ-alumina nanosheets. Specifically:

[0127] (1) Preparation of γ-alumina nanosheets:

[0128] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;

[0129] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral. The product was then dried in a vacuum oven at 30°C for 4 h, 60°C for 8 h, and 80°C for 12 h to obtain the first product.

[0130] The first product is placed in a muffle furnace in an air atmosphere and sintered in the following stages:

[0131] Stage I: Heating from room temperature to 120 °C at a rate of 10 °C / min, and keeping at this temperature for 0.5 h;

[0132] Stage II: Heating to 300 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0133] Stage III: heating to 450 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0134] Stage IV: Heat to 600 °C at a rate of 10 °C / min and keep at this temperature for 0.5 h; then cool naturally to room temperature.

[0135] After the above steps are completed, the γ-alumina nanosheets are prepared for use.

[0136] (2) Dissolve 5 g of polypropylene pellets in 500 mL of xylene at 100°C to obtain a first solution; dissolve 0.05 g of the γ-alumina nanosheets prepared in step (1) in 10 ml of xylene (the mass of the γ-alumina nanosheets is 1 wt% of the total mass of the polypropylene and the γ-alumina nanosheets), and disperse them by ultrasonic dispersion for 2 h to obtain a suspension containing γ-alumina nanosheets; use a pipette to drop the above suspension of γ-alumina nanosheets into the first solution one by one, stir for 2 h, and obtain a second solution; after the reaction is completed, pour the obtained product into acetone for filtration, and use a Soxhlet extractor to extract in a deionized water environment for 24 h, and then freeze-dry for 48 h to obtain a polypropylene-based composite.

[0137] (3) A circular cutter with a diameter of 50 mm was used to cut a number of circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm. A second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film. 0.2 g of the biaxially oriented composite material was placed in the circular holes of the first polyimide film. A third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it. Then, a flat-plate vulcanizer was used for hot pressing treatment. The temperature was set to 210 °C, the pressure was set to 15 MPa, the processing time was set to 10 min, the number of exhaust times was set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene-based composite film.

[0138] Example 3

[0139] A polypropylene-based composite film was prepared in a similar manner to Example 1, except that the mass of the γ-alumina nanosheets was 3 wt % of the total mass of the polypropylene and the γ-alumina nanosheets. Specifically:

[0140] (1) Preparation of γ-alumina nanosheets:

[0141] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;

[0142] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral. The product was then dried in a vacuum oven at 30°C for 4 h, 60°C for 8 h, and 80°C for 12 h to obtain the first product.

[0143] The first product is placed in a muffle furnace in an air atmosphere and sintered in the following stages:

[0144] Stage I: Heating from room temperature to 120 °C at a rate of 10 °C / min, and keeping at this temperature for 0.5 h;

[0145] Stage II: Heating to 300 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0146] Stage III: heating to 450 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0147] Stage IV: Heat to 600 °C at a rate of 10 °C / min and keep at this temperature for 0.5 h; then cool naturally to room temperature.

[0148] After the above steps are completed, the γ-alumina nanosheets are prepared for use.

[0149] (2) Dissolve 5 g of polypropylene pellets in 500 mL of xylene at 100°C to obtain a first solution; dissolve 0.15 g of the γ-alumina nanosheets prepared in step (1) in 10 ml of xylene (the mass of the γ-alumina nanosheets is 3 wt% of the total mass of the polypropylene and the γ-alumina nanosheets), and disperse them by ultrasonic dispersion for 2 h to obtain a suspension containing γ-alumina nanosheets; use a pipette to drop the above suspension of γ-alumina nanosheets into the first solution in turn, stir for 2 h, and obtain a second solution; after the reaction is completed, pour the obtained product into acetone for filtration, and extract it in a deionized water environment for 24 h using a Soxhlet extractor, and then freeze-dry it for 48 h to obtain a polypropylene-based composite.

[0150] (3) A circular cutter with a diameter of 50 mm was used to cut a number of circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm. A second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film. 0.2 g of the biaxially oriented composite material was placed in the circular holes of the first polyimide film. A third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it. Then, a flat-plate vulcanizer was used for hot pressing treatment. The temperature was set to 210 °C, the pressure was set to 15 MPa, the processing time was set to 10 min, the number of exhaust times was set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene-based composite film.

[0151] Example 4

[0152] A polypropylene-based composite film was prepared in a similar manner to Example 1, except that the mass of the γ-alumina nanosheets was 5 wt % of the total mass of the polypropylene and the γ-alumina nanosheets. Specifically:

[0153] (1) Preparation of γ-alumina nanosheets:

[0154] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;

[0155] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral. The product was then dried in a vacuum oven at 30°C for 4 h, 60°C for 8 h, and 80°C for 12 h to obtain the first product.

[0156] The first product is placed in a muffle furnace in an air atmosphere and sintered in the following stages:

[0157] Stage I: Heating from room temperature to 120 °C at a rate of 10 °C / min, and keeping at this temperature for 0.5 h;

[0158] Stage II: Heating to 300 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0159] Stage III: heating to 450 °C at a rate of 10 °C / min and keeping at this temperature for 0.5 h;

[0160] Stage IV: Heat to 600 °C at a rate of 10 °C / min and keep at this temperature for 0.5 h; then cool naturally to room temperature.

[0161] After the above steps are completed, the γ-alumina nanosheets are prepared for use.

[0162] (2) Dissolve 5 g of polypropylene pellets in 500 mL of xylene at 100°C to obtain a first solution; dissolve 0.25 g of the γ-alumina nanosheets prepared in step (1) in 10 ml of xylene (the mass of the γ-alumina nanosheets is 5 wt% of the total mass of the polypropylene and the γ-alumina nanosheets), and disperse them by ultrasonic dispersion for 2 h to obtain a suspension containing γ-alumina nanosheets; use a pipette to drop the above suspension of γ-alumina nanosheets into the first solution one by one, stir for 2 h, and obtain a second solution; after the reaction is completed, pour the obtained product into acetone for suction filtration, and use a Soxhlet extractor to extract in a deionized water environment for 24 h, and then freeze-dry for 48 h to obtain a polypropylene-based composite.

[0163] (3) A circular cutter with a diameter of 50 mm was used to cut a number of circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm. A second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film. 0.2 g of the biaxially oriented composite material was placed in the circular holes of the first polyimide film. A third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it. Then, a flat-plate vulcanizer was used for hot pressing treatment. The temperature was set to 210 °C, the pressure was set to 15 MPa, the processing time was set to 10 min, the number of exhaust times was set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene-based composite film.

[0164] Comparative Example 1

[0165] 0.05 mol of aluminum sulfate 18hydrate powder was dissolved in 50 mL of deionized water at room temperature and stirred at 1500 r / min for 3 h; then the pH value of the solution was adjusted to 5 with ammonia water and stirred with a stirring rod for 30 min to obtain a suspension;

[0166] The suspension was transferred to a 100 mL stainless steel autoclave with a Teflon liner and subjected to hydrothermal treatment at 190°C for 24 h. The obtained product was then separated by filtration and washed with deionized water until neutral. The product was then dried in a vacuum oven at 30°C for 4 h, 60°C for 8 h, and 80°C for 12 h to obtain the first product.

[0167] The obtained first product was placed in a muffle furnace with a nitrogen atmosphere, and the temperature was increased from room temperature to 600°C at a heating rate of 10°C / min, and kept warm for 3 h; then it was naturally cooled to room temperature to obtain γ-alumina nanosheets.

[0168] Figure 1 (a) shows one of the TEM characterizations of the γ-alumina nanosheets prepared in Example 1, in which the thickness of the γ-alumina nanosheets prepared is marked. It can be seen that its length is between 119 and 163 nanometers, and it is obvious that the structure of the γ-alumina nanosheets is complete, which is due to the step sintering method to prevent the intermediate product from breaking during the rapid heating process, thereby obtaining a complete nanosheet structure; Figure 1 (b) shows the second TEM characterization of the γ-alumina nanosheets prepared in Example 1, in which the thickness of the γ-alumina nanosheets prepared is marked. It can be seen that its thickness is between 8 and 10 nanometers. Figure 1 (c) shows the TEM characterization of the γ-alumina nanosheets prepared in Comparative Example 1, and it is obvious that the structure of the γ-alumina nanosheets prepared in Example 1 is more complete and clear.

[0169] Comparative Example 2

[0170] A circular cutter with a diameter of 50 mm was used to cut several circular holes with a diameter of 5 cm on a first polyimide film with a thickness of 100 μm, a second polyimide film with a thickness of 100 μm was placed on the bottom of the first polyimide film, 0.2 g of polypropylene pellets were placed in the circular holes of the first polyimide film, a third polyimide film with a thickness of 100 μm was placed on top of the first polyimide film to encapsulate it, and then a flat-plate vulcanizer was used for hot pressing treatment, the temperature was set to 210°C, the pressure was set to 15 MPa, the processing time was set to 10 min, the number of exhaust times was set to 15 times, and the exhaust time for each time was set to 10 s, to obtain a polypropylene film.

[0171] Figure 2The dielectric constant and material loss spectrum comparison diagram of the polypropylene-based composite films prepared in Examples 1-4 and the polypropylene film prepared in Comparative Example 2 is shown. It can be seen from the figure that the dielectric constants of the polypropylene-based composite films prepared in Examples 1-4 are between 2.2 and 2.45, and the dielectric constant of the polypropylene-based composite film prepared in Example 4 reaches 2.45, which is 11.36% higher than that of the polypropylene film prepared in Comparative Example 2. The dielectric loss of the polypropylene-based composite film prepared in Examples 1-2 is kept at the order of 1E-3, which is close to the loss order of the polypropylene-based composite film prepared in Comparative Example 2.

[0172] Figure 3 The Weibull distribution diagram of DC breakdown of the polypropylene-based composite films prepared in Examples 1-4 and the polypropylene film prepared in Comparative Example 2 is shown. It can be seen from the figure that the breakdown field strength values ​​of the polypropylene-based composite films prepared in Example 1 and Example 2 are 625 kV / mm and 603 kV / mm, respectively, which are 8.89% and 5.05% higher than the breakdown field strength values ​​of Comparative Example 2. The breakdown field strength values ​​of the polypropylene-based composite films prepared in Example 3 and Example 4 are 576 kV / mm and 481 kV / mm, respectively, wherein the breakdown field strength values ​​of the polypropylene-based composite film prepared in Example 4 are reduced by 16.2% compared with the polypropylene film prepared in Comparative Example 2. Based on the above examples, the polypropylene-based composite film prepared in Example 1 has the best performance.

[0173] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A polypropylene-based composite, characterized in that: The composite includes 95-99.5 wt % of polypropylene and 0.5-5 wt % of gamma alumina nanosheets.

2. The composite according to claim 1, characterized in that Preferably, the length of the γ-alumina nanosheets is 119-163 nanometers.

3. The composite according to claim 1, characterized in that The thickness of the γ-alumina nanosheet is 8-10 nanometers.

4. The composite according to claim 1, characterized in that The composite is obtained by in-situ compounding of γ-alumina nanosheets into polypropylene.

5. A method for preparing the composite according to any one of claims 1 to 4, characterized in that: The method comprises: Step 1, dissolving polypropylene pellets in an organic solvent to obtain a first solution; Step 2, adding a suspension containing γ-alumina nanosheets to the first solution to obtain a second solution; Step 3, purifying the second solution to obtain the complex.

6. The method according to claim 5, characterized in that In step 1, the organic solvent is selected from one or more of decahydronaphthalene, toluene and xylene.

7. The method according to claim 5, characterized in that In step 1, the dissolution temperature of the polypropylene pellets in the organic solvent is 90-110°C.

8. The method according to claim 5, characterized in that In step 3, the purification includes: filtration, extraction and drying.

9. The method according to claim 8, characterized in that Filter with acetone.

10. Use of the composite according to any one of claims 1 to 3 or the composite obtained by the method according to any one of claims 4 to 9 in polypropylene-based composite films.

Citation Information

Patent Citations

  • Flaky nano gamma-Al2O3 and preparation method thereof

    CN104556177A

  • Method for preparing polypropylene / nano composite dielectric with high direct current breakdown field strength

    CN107163401A

  • High-temperature-resistant polypropylene composite dielectric material based on oil-phase Al2O3 nanocrystals and preparation method of high-temperature-resistant polypropylene composite dielectric material

    CN117264254A

  • Aluminum-oxide-forming composition and method for producing same, and polyolefin-based polymer nanocomposite containing zinc oxide particles or aluminum oxide particles and method of producing same

    US20190276612A1